Analisis Kesulitan Belajar Siswa Pada Materi Perkalian Dalam Bentuk Cerita Kelas III SD N 2 Cihonje - Khoirun Nisa, Tsania; Badarudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT The study was conducted with the objective of identifying and analyzing the learning difficulties experienced by students in the third grade of SD Negeri 2 Cihonje in solving mathematical story problems on multiplication and to identify the factors causing these difficulties. The background of this study stems from the phenomenon that many elementary school students still consider mathematics to be a difficult subject, especially when presented in the form of story problems that require a combination of literacy and numeracy skills. A qualitative approach was applied in this study, utilizing a descriptive method to present the findings. The subjects in this study were four third-grade students selected through purposive sampling and one classroom teacher. This study employed interviews, observations, and documentation as instruments of data collection, while the analysis was conducted through the processes of reducing, presenting, and interpreting the data. The results of the study show that students face difficulties in five stages according to Newman's framework: reading, comprehension, transformation, process skills, and writing the final answer. These difficulties are influenced by internal factors, including intellectual, emotional, and physiological aspects, as well as external factors, such as teaching strategies and family environment. These findings highlight that learning difficulties in multiplication word problems are multidimensional, requiring contextual, interactive, and adaptive teaching strategies, along with family support, to improve students' conceptual understanding and confidence in learning mathematics. Keywords: learning difficulties, story problems, multiplication ABSTRAK Analisis terhadap hambatan yang dialami oleh peserta didik kelas III di SD Negeri 2 Cihonje dalam menyelesaikan soal cerita matematika pada topik perkalian menjadi fokus utama penelitian ini, sekaligus pengungkapan variabel-variabel yang berkontribusi terhadap kesulitan tersebut. Latar belakang penelitian ini berangkat dari fenomena terkait masih banyaknya siswa SD masih beranggapan bahwa matematika sebagai pelajaran yang sulit, terutama ketika disajikan dalam bentuk soal cerita yang menuntut keterpaduan keterampilan literasi dan numerasi. Teknik deskriptif dipilih sebagai pendeketan pada studi ini. Subjek dalam penelitian yaitu 4 siswa kelas tiga yang dipilih secara purposive sampling serta satu guru kelas. Data dikumpulkan menggunakan pedoman wawancara, lembar observasi, dokumentasi dan dianalisis melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menyatakan bahwasanya para peserta didik menghadapi kesulitan pada lima tahap menurut kerangka kerja Newman: membaca, pemahaman, transformasi, keterampilan proses, dan penulisan jawaban akhir. Kesulitan-kesulitan ini dipengaruhi oleh faktor internal, termasuk aspek intelektual, emosional, dan fisiologis, dan faktor eksternal, seperti lingkungan keluarga beserta strategi pengajaran. Temuan ini menyoroti bahwa kesulitan belajar dalam soal cerita perkalian bersifat multidimensi, memerlukan strategi pengajaran yang kontekstual, interaktif, dan adaptif, bersama dengan dukungan keluarga, untuk meningkatkan pemahaman konseptual siswa, dan kepercayaan diri dalam mempelajari matematika.